Obtaining of transgenic potato (Solanum tuberosum L.) cultivar IPB CP3 containing LYZ‐C gene resistant to bacterial wilt disease - Pasmawati Pasmawati; Aris Tjahjoleksono; Suharsono Suharsono (Indonesian Journal of Biotechnology, 2021)
Bacterial wilt caused by Ralstonia solanacearum is one of the most important bacterial diseases in potato production. This study aimed to obtain the transgenic potato (Solanum tuberosum L.) cultivar IPB CP3, containing LYZ‐C gene encoding for lysozyme type C, resistant to bacterial disease caused by R. solanacearum. Genetic transformation using Agrobacterium tumefaciens LBA4404 to 124 internode explants resulted in the transformation efficiency of about 47.58% with a regeneration efficiency of approximately 30.51%. Gene integration analysis showed that 16 clones were confirmed as transgenic clones containing the LYZ‐C gene. Analysis of resistance to R. solanacearum of three transgenic clones showed that all three transgenic clones were more resistant than a non‐transgenic one. This result showed that the LYZ‐C gene integrated in the genome of transgenic potato increased the resistance of potato plants to R. solanacearum. We obtained two transgenic clones considered resistant to bacterial wilt disease.